The Influence Of The Mind Mapping Model On Learning Outcomes In Clean Air Material At Elementary School - Minar Trisnawati Tobing; Eva Pasaribu; Lisbet Sihombing (LPPM Universitas PGRI Sumatera Barat, 2024)
This research aims to see the influence of the mind mapping model on learning outcomes in clean air material at SD GKPS Rambung Merah. This type of research is experimental research. Experimental research is a research method used to find the effect of certain treatments on others under controlled conditions. There are 4 forms of experimental methods, namely: Pre-Experimental, True-Experimental, Factorial Experimental, Quasi Experimental. The design used in this research is Pre Experimental in the form of One Group Pretest-Posttest Design. The population and sample in this research were class V students of GKPS 1 Rambung Merah, totaling 30 people. Based on the SPSS calculation results obtained above, it is known that the significant value is 0.000 < 0.05, so Ho is rejected and Ha is accepted by comparing t count > t table with df = n-1, namely 12,577 > 2,045. It can be concluded that there is an influence of the Mind Mapping model on student learning outcomes on the theme Clean Air for Health, Subtheme How the Body Processes Clean Air in Class V GKPS Rambung Merah.